KARAKTERISTIK FAKTOR RISIKO MENINGITIS BAKTERIAL PADA NEONATUS DI RSUP PROF. DR. I.G.N.G NGOERAH DENPASAR - Sampe, Dhea Gracia Eliani; Mahalini, Dewi Sutriani; Witarini, Komang Ayu (Universitas Udayana, 2024)
Bacterial meningitis in neonates is inflammation of the meninges in response to bacteria that can occur during the first 28 days of life. Bacterial meningitis is a serious problem causing neonatal deaths with various influencing factors. This research was conducted to obtain data regarding the characteristics of risk factors for bacterial meningitis in neonates at RSUP Prof. Dr. IGNG Ngoerah Denpasar. This study is retrospective, and data was taken from medical records of neonatal patients treated in the 2021-2022 period. Data are presented descriptively with sample determination using a total sampling technique. From a total of 45 samples that met the inclusion and exclusion criteria, it was found that most cases of neonatal bacterial meningitis occurred at premature gestational age <37 weeks (64.4%), 0-72 hours age group (64.4%), male gender. (51.1%), low birth weight <2500 grams (64.4%), history of asphyxia (51.1%), clinical respiratory distress (82.2%), clinical neonatal sepsis (100%), clinical jaundice neonatorum (68.9%), and use of ventilator/NIV/CPAP (82.2%). However, in this study, only distribution was obtained based on premature rupture of membranes (20%), intrauterine infection (35.6%), congenital abnormalities (26.7%), and neonates with clinical seizures (6.7%). Based on the research results, it can be concluded that the characteristic risk factors for neonates with bacterial meningitis, namely birth to mothers with preterm or premature gestational age, are more common in neonates aged 0-72 hours, which are associated with clinical EONS, male gender, LBW, history of asphyxia, clinical respiratory distress, clinical neonatal jaundice, and use of ventilator/NIV/CPAP. Keywords : Neonatal bacterial meningitis, characteristics, risk factors